A new approach for the synthesis of bisindoles through AgOTf as catalyst - Beltrá, Jorge; Gimeno, M. Concepción; Herrera, Raquel P. (Beilstein Journal of Organic Chemistry, 2014)
A novel approach for the catalyzed formation of bisindolylmethane derivatives (BIMs) is described. This methodology is the unique example where AgOTf has been successfully used for the activation of aldehydes, giving easy access to a broad range of bisindolyl derivatives with excellent results. Moreover, the simplicity and easy operational methodology using a small amount of commercially available AgOTf (1–3 mol %), one of the lowest catalytic charge used in this process to date, makes this procedure an alternative approach for this interesting and appealing reaction.
Keywords: Ag(I); aldehydes; bisindole; catalysis; indole